A METHOD TO MANAGE MISSION CREEP IN CREDIT UNIONS NAVIGATING RAPID DEVELOPMENT - Roderick Macdonald (Jurnal Ilmiah Ekonomi Bisnis, 2012)
The senior administrators of credit unions in rapidly developing regions shouldactively manage the evolution of their mission. Doing so requires a minimal effort thatwill bring a more systematic understanding of their membership, and afford themfinancial success while remaining faithful to their foundational charisma. The objectiveof the study is to discuss the method to manage mission creep in credit unions.Key Words: mission creep, credit unions,